Efficacy of bio-fertilizers and mulching on growth, yield and quality of strawberry (Fragaria × ananassa) cv. Chandler - TRIPATHI, V K; JAIN, ANKITA; KUMAR, SANJEEV; DUBEY, VISHAL; KUMAR, ABHINAV (The Indian Journal of Agricultural Sciences, 2017)
A study was undertaken to examine the efficacy of bio-fertilizers and mulching on growth, yield and quality of strawberry (Fragaria × ananassa Duch.) cv. Chandler during two successive years, i.e. 2012-13 and 2013-14 at Kanpur (Uttar Pradesh), India. The experiment was laid out in randomized block design with three replications and ten treatments. One year old runners were used for planting. Significantly increase in plant height (19.20 and 18.70 cm), number of leaves (17.15 and 16.75), number of runners (2.28 and 2.17) and number of crowns (2.78 and 2.64) per plant, whereas minimum number of days (66.00 and 65.33 days) to produce first flower, maximum number of flowers (16.18 and 15.87) and fruits set (15.13 and 14.72) per plant during both the years of experimentation was observed with strawberry plants treated with Azotobacter 7 kg/ha+black polythene mulch. Maximum duration of harvesting (67.85 and 67.00 days) with higher yield (109.12 and 107.00 g/plant) of berries was also recorded with Azotobacter 7 kg/ha+black polythene mulch treated plants in both the years. As far the quality characters of berries are concerned, strawberry plants produced berries of significantly maximum length (2.92 and 2.90 cm), width (1.83 and 1.79 cm), weight (7.15 and 7.11g), volume (4.39 and 4.36 cc), TSS (7.19 and 7.16 0Brix), total sugars (5.63 and 5.60 %) and ascorbic acid (56.13 and 56.00 mg/100g pulp) with minimum acidity (0.250 and 0.249%) when treated with Azotobacter 7 kg/ha+black polythene mulch in northern plains of India.